Mathematics communication of students in agriculture area - A Kausar; E Nurlaelah; K Kusnandi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Mathematics communication is an important cognitive ability, especially students who live in area which geographically located in agriculture zone. This research aims to see and analyze mathematics communication of students in senior high school increased with agriculture based mathematics learning. This research is quasi-experiment involve a school in zone with good agriculture potential. Result of this experiment showed that mathematics communication of students who have high and medium ability in mathematics learning increased through agriculture based mathematics learning. But it was not have effect to students with low ability in mathematics learning.